TECHNOLOGIES FOR IMPROVING THE LINGUISTIC AND DIDACTIC POSSIBILITIES OF DEVELOPING THE SKILLS OF ADAPTING TO SOCIO-CULTURAL CHANGES IN STUDENTS (AS AN EXAMPLE OF TEACHING THE RUSSIAN LANGUAGE)" (Proceedings of International Educators Conference, 2024)
This article describes the issues of improving the linguistic and didactic possibilities of developing the skills of adapting to social and cultural changes in students on the example of teaching the Russian language.